Kajian Potensi Pariwisata dalam Bentuk Budaya dan Kehidupan Sosial di Bangka Belitung dalam Novel Laskar Pelangi Karya Andrea Hirata (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The mutual influence relationship between literature and tourism occurs in creative inspiration and destination promotion. An interdisciplinary approach is needed to understand the contributions of both. Laskar Pelangi, by Andrea Hirata, is an example of literary success in promoting Bangka Belitung. This research aims to examine the tourism values in this novel and in the context of how literary works are able to increase the popularity of the destination. This research uses qualitative methods with a hermeneutical approach. The findings of this research conclude that the value of tourism in the novel Laskar Pelangi is reflected through natural beauty, cultural richness and emotional experiences. This has the potential to increase the popularity of tourist destinations, especially in Bangka Belitung.